Há assimetria no repasse dos juros bancários de variaç\~oes na taxa Selic? - Pedro Castro; Jo\~ao Manoel Pinho de Mello (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2010)
– This paper tests and find evidence that support the view that credit interest rates respond more to increases than to decreases in the Central Bank basic interest rate (Selic). This asymmetry is robust to an event analysis, in which the availability of a dataset containing daily information is explored in order to isolate monetary policy shocks on interest rates as the cause of the assymetric response of interest rates, as a shift in the basic interest rate is akin to an increase in marginal cost and thus corresponds to a shift in the supply curve of banks. The econometric identification hypothesis is that banks (supply) react faster to monetary shocks than consumers (demand for credit). The empirical evidence of greater rigidity to Selic decreases contributes to the literature of bank behavior in credit markets and the transmission mechanism of monetary policy in Brazil.
Keywords: L11; G21; 330; Microeconomics of Banking; interest pass-through and Adverse Selection JEL Codes: L11; G21